2021
DOI: 10.1002/nop2.1031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic illness resources on self‐management and the mediating effect of patient activation among patients with coronary heart disease

Abstract: Coronary atherosclerotic heart disease, also referred to coronary heart disease (CHD), is a common type of cardiovascular disease and a major public concern in China (Bai and Wang, 2019). During the last decade, the death number of global cardiovascular disease has increased by 12.5%, and in 2017, cardiovascular disease accounts for one third of global human death (GBD, 2018). The trend of the prevalence of chronic diseases in China from 2018-2025 shows that the prevalence of CHD is still on the rise (from 161… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…However, the support provided to hypertensive stroke patients from surrounding chronic illness resources was poor at 6 months after discharge. Similar results have been found in studies of patients with diabetes and coronary heart disease (12,13). The provision of support by chronic illness resources in our study was better than that in a study conducted in the Xinjiang region of China ( 13).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, the support provided to hypertensive stroke patients from surrounding chronic illness resources was poor at 6 months after discharge. Similar results have been found in studies of patients with diabetes and coronary heart disease (12,13). The provision of support by chronic illness resources in our study was better than that in a study conducted in the Xinjiang region of China ( 13).…”
Section: Discussionsupporting
confidence: 87%
“…) (17). The previous study found that correlation coefficient between chronic illness resources and self-management in patients with coronary heart disease was 0.411 (12). With a power of 0.80 and α error of 0.05, the minimum sample size for the study had to be 87.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Zhong et al (2016) found that the use of chronic illness resources of patients with diabetes was positively correlated with the self‐management including diet, exercise, medicine, glucose monitoring, foot care and dealing with hyperglycaemia and hypoglycaemia. Another study of middle‐aged and older patients with coronary heart disease revealed a positive correlation between chronic illness resource and self‐management behaviour (Zhang, Chen, et al, 2021). Chronic illness resources differ from traditional support and include resources from family and friends, the healthcare team, neighbourhood, media and policy and the workplace (Glasgow et al, 2000).…”
Section: Discussionmentioning
confidence: 99%